2016
DOI: 10.1098/rstb.2015.0117
|View full text |Cite
|
Sign up to set email alerts
|

Species variation in the degree of sex differences in brain and behaviour related to birdsong: adaptations and constraints

Abstract: One contribution of 16 to a theme issue 'Multifaceted origins of sex differences in the brain'.Subject Areas: behaviour, evolution, neuroscience Keywords: sexual selection, song-control system, HVC, canary Author for correspondence: Gregory F. Ball e-mail: gball@umd.edu Species variation in the degree of sex differences in brain and behaviour related to birdsong: adaptations and constraints The song-control system, a neural circuit that controls the learning and production of birdsong, provided the first examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 62 publications
1
32
0
2
Order By: Relevance
“…In this issue, Ball [51] discusses the potential power of studies on birds owing to the enormous natural variation across the approximately 6000 existing song bird species that live in different climates and habitats and are thus subject to divergent selection. Early studies confirmed a correlative relationship between the degree of sexual dimorphism in the size of song control nuclei and sex differences in song production.…”
Section: Neuroanatomical Versus Behavioural Sex Differencesmentioning
confidence: 99%
“…In this issue, Ball [51] discusses the potential power of studies on birds owing to the enormous natural variation across the approximately 6000 existing song bird species that live in different climates and habitats and are thus subject to divergent selection. Early studies confirmed a correlative relationship between the degree of sexual dimorphism in the size of song control nuclei and sex differences in song production.…”
Section: Neuroanatomical Versus Behavioural Sex Differencesmentioning
confidence: 99%
“…The best known differences are sexual dimorphisms in the size and composition of the song-control nuclei, which regulate song learning and production and are typically larger in males [Nottebohm and Arnold, 1976;Arnold, 1992;Ball and MacdougallShackleton, 2001;Ball, 2016]. However, researchers have also detected effects of sex on gene expression and protein levels in the songbird auditory system as well as on auditory perception [Phillmore et al, 2003;Ikebuchi et al, 2003;Pinaud et al, 2006;Krentzel and Remage-Healey, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The song nucleus was the first anatomical sexual dimorphism in the vertebrate brain to be linked to a sexually dimorphic learned motor behaviour [28]. The song nucleus is considerably larger in males of species in which only males sing; in duetting species the dimorphism is not as pronounced (for a recent review, see [29]). The anatomical sexual dimorphism of the song nuclei is paralleled by sex differences in expression of the CNTNAP2 gene during development and in the adult [30].…”
Section: Evolutionary Pressures For Sex Differences In Learningmentioning
confidence: 99%